2006
DOI: 10.1001/archsurg.141.12.1246
|View full text |Cite
|
Sign up to set email alerts
|

Induction Chemoradiation for Rectal Cancer

Abstract: To review the application, outcome, and recent developments of neoadjuvant chemoradiation therapy with respect to rectal cancer. Data Sources and Study Selection: Articles written in English after 1980 selected from MEDLINE and PubMed from the National Library of Medicine. Case reports were excluded. There were no other criteria for exclusion of published information pertaining to this topic. Data Extraction and Synthesis: Articles were obtained and organized from MEDLINE and PubMed as well as the reference li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…10 Recently, preoperative chemoradiation therapy for low rectal cancer has been shown to increase the probability of tumor resectability, improve sphincter preservation rate, decrease local recurrence, and improve both disease-free and overall survival. [11][12][13] However, recent studies have reported that operating time, blood loss, and the postoperative complication rate increase in TME with preoperative irradiation. [14][15][16] However, there are few reports about the effect of preoperative chemoradiation therapy on laparoscopic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…10 Recently, preoperative chemoradiation therapy for low rectal cancer has been shown to increase the probability of tumor resectability, improve sphincter preservation rate, decrease local recurrence, and improve both disease-free and overall survival. [11][12][13] However, recent studies have reported that operating time, blood loss, and the postoperative complication rate increase in TME with preoperative irradiation. [14][15][16] However, there are few reports about the effect of preoperative chemoradiation therapy on laparoscopic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…1 This combined modality approach has led to a reduction in local recurrence rates and an increase in sphincter preservation, presumably because of tumor down-staging before surgery. 2 However, patients whose tumors fail to respond to neoadjuvant therapy may not derive any benefit.…”
mentioning
confidence: 99%
“…This assessment is usually done several weeks after the therapy so that an appreciable reduction in tumor size can be observed; however, metastasis might also occur during this time interval. In addition, a large proportion of early-stage patients still develop distant metastasis even though they undergo surgical removal of the tumor mass [6]. Consequently, a reliable method to detect cancer cells prior to metastatic tumor formation could improve the treatment decisions for colorectal cancer patients.…”
Section: Introductionmentioning
confidence: 99%